Defect-based characterization of the fatigue behavior of additively manufactured titanium aluminides. (October 2022) - Teschke, M.; Moritz, J.; Tenkamp, J.; Marquardt, A.; Leyens, C.; Walther, F.
Highlights: Mechanical and microstructural characterization of additively manufactured TiAl. Effect of manufacturing-related defects on the fatigue behavior. Model-based description and validation of defect-dependent fatigue behavior. Representation is independent of defect type, size, and test temperature. Visualization of the influence of theoretical defects with synthetic S-N curves. Abstract: The additively manufactured titanium aluminide alloy TNM-B1 was characterized microstructurally and mechanically in the as-built and hot isostatically pressed (HIP) condition. Tensile and constant amplitude tests were performed at room temperature and 800 °C. Using fractographic SEM images, the fracture-inducing defect was identified. With the HIP, defect number and size could be reduced, increasing fatigue strength by 43% to 500 MPa. Using the model approaches of Murakami and Shiozawa, the fatigue life was correlated with the local stress intensity factor and could be described as function of the stress amplitude as well as the size and location of fracture-inducing defects.